PENYIMPANGAN SOSIAL DALAM MASYARAKAT :ANALISIS PERSEPEKTIF SOSIOLOGI TERHADAP TEORI ANOMI EMILE DURKHEM - Akdila Bulanov,M.Si; Aidil Fikri; Asyifa Az-zahra; Rahmatul Hasanah; Salwa Baihaki (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Social deviation is a behavior that does not conform to the norms and values prevailing in society. This phenomenon can be found in various forms, such as juvenile delinquency, drug abuse, criminal acts, corruption, and other deviant behaviors that have the potential to disrupt social order. This article aims to analyze the forms of social deviation in society through a sociological perspective using the anomie theory proposed by Emile Durkheim. According to Durkheim, anomie is a condition in which social norms and rules weaken, causing individuals to lose their behavioral guidelines. The method used in this article is a literature review, examining various sources related to social deviation and the theory of anomie. The study's results indicate that rapid social change, weak social control, and the discrepancy between societal goals and the available means to achieve them can encourage the emergence of various forms of social deviation. Therefore, the strengthening of values, norms, and social control is necessary to maintain order and harmony in community life. This study is expected to provide an understanding of the factors causing social deviation and the importance of the community's role in preventing deviant behavior